Kearifan dalam Bahasa Sebuah Tinjauan Pragmatis terhadap Profil Kebahasaan Media Massa pada Masa Pasca Order Baru - Rahyono, F X; Sutanto, Irzanti; Rachmat, Ratnawati; Puspitorini, Dwi (UI Scholars Hub, 2005)
The Wisdom of Language A Pragmatic Study on the Profile of the Post-New Order Era Mass Media Language. “Total Reformasi!” is the slogan circulated in the public discourse of the post-New Order era. All kinds of condemnation, grievances, and anger have been raised in various discourses, from formal to informal dialogues. In such an era, people’s collective memory is mostly associated with uncontrollable events, and it is eventually represented in the discourse of “the overdosed Reformasi” (Reformasi yang kebablasan). A word, phrase, and sentence basically have the potential of expressing both referential and contextual meanings. From a pragmatic point of view, a word, phrase, or sentence has a capacity to express either wise or unwise intentions. “Unwise intention” in the context of this research is defined as an act of transgressing or violating the ethics and etiquettes of a society. How can the discourse of Reformasi be constructed wisely? Is it necessary to appropriate unwise vocabulary in public discourses? Who holds the responsibility for fostering public wisdom? The wisdom of language has nothing to do whatsoever with manipulative acts in information dissemination. The wisdom of language relates to strategies of choosing certain linguistic features. Wisdom is a collective responsibility. A wise language would not be able to fully exist unless all of the related parties and resulting events make a concerted effort towards wisdom. Wisdom does not involve itself in the tug of war between the right and freedom of participating in discursive formations.